Co-Designing Technology for Aging in Place: A Systematic Review. (7th June 2020) - Sumner, Jennifer; Chong, Lin Siew; Bundele, Anjali; Wei Lim, Yee
Abstract: Background and Objectives: There is a growing interest to involve older adults in the co-design of technology to maintain their well-being and independence. What remains unknown is whether the beneficial effects of co-designed solutions are greater than those reported for non co-designed solutions. The aim of this study was to evaluate the effects and experiences of co-designed technology that support older adults to age in place. Research Design and Methods: We conducted a systematic review to (a) investigate the health and well-being outcomes of co-designed technology for older adults (≥60 years), (b) identify co-design approaches and contexts where they are applied, and (c) identify barriers and facilitators of the co-design process with older adults. Searches were conducted in MEDLINE, EMBASE, CINAHL, Science Citation Index (Web of Science), Scopus, OpenGrey, and Business Source Premiere. Results: We identified 14, 649 articles and included 34 projects. Four projects reported health and well-being outcomes; the effects were inconsistent. Co-design processes varied greatly and in their intensity of older adult involvement. Common facilitators of and barriers to co-design included the building of relationships between stakeholders, stakeholder knowledge of problems and solutions, and expertise in the co-design methodology. Discussion and Implications: The effect of co-designed technology on health and well-being was rarely studied and it was difficult to ascertain its impact. Future co-design efforts need to address barriers unique to older adults. Evaluation of the impact of co-designed technologies is needed and standardization of the definition of co-design would be helpful to researchers and designers.